Factors constituting working environment and their impact on employee productivity at Majlis Perbandaran Jasin (MPJ) / Nur’athiqah Ramlee and Nursyahirah Roswandi - Ramlee, Nur’athiqah; Roswandi, Nursyahirah (Faculty of Business and Management, 2016)
Employee was the vital activator for every organization existed in this world. Without employee, an organization would paralyze and could not operate normally since there is no manpower to run the task and duty. However, having poor performance manpower also would jeopardize the organization’s operation and standard since this individual will not be able to contribute profit to the company. To become competitive organization, first and foremost, the employee’s performance must be in excellent level. That is why it is important to every manager to understand the situation that could affect their employee performance or productivity in both positive and negative way. Hence through this will make the manager more understand on that. As for Majlis Perbandaran Jasin, researcher is eager to identify what are the factors constituting working environment that impact the employee productivity. The first research objective is to identify the relationship between supervisor support and employee’s productivity. Second research objective are, to identify the relationship between training and development and employee’s productivity. The last objectives are to identify the relationship between adequate workload and employee’s productivity. Total of 138 respondents were answering the questionnaires. Data were collected and interpreted into the valuable data through the frequency’s analysis, descriptive statistics, correlational analysis and regression analysis. These findings has supported all three objectives however only two hypothesis were accepted which are the H2 and H3, whereas the H1 for supervisor support factors was unaccepted.